2018 17th IEEE International Conference on Trust, Security and Privacy in Computing and Communications/ 12th IEEE International 2018
DOI: 10.1109/trustcom/bigdatase.2018.00274
|View full text |Cite
|
Sign up to set email alerts
|

Let me Join Two Worlds! Analyzing the Integration of Web and Native Technologies in Hybrid Mobile Apps

Abstract: We can notice that security problems of inappropriate integration of native and web technologies in hybrid mobile applications (apps) have been covered in the related state-of-theart research. However, analyzing hybrid mobile apps' unique behaviors has been seldom addressed. In this paper, we explore the influence of native and web technologies integration in hybrid mobile apps on the generated profile of mobile applications. Specifically, we analyze type of Security Sensitive APIs (SS-APIs) exposed to web con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…During the analysis of the state of art, before making the decision to conduct our research, we also found some interesting studies showing how to migrate applications in native technology to hybrid technology [25], and the possibilities of combining these two worlds [26,27]. Although these are very interesting articles, they do not deal with the content of interest to us at all in terms of the application of these technologies to our energy-saving projects.…”
Section: Introductionmentioning
confidence: 99%
“…During the analysis of the state of art, before making the decision to conduct our research, we also found some interesting studies showing how to migrate applications in native technology to hybrid technology [25], and the possibilities of combining these two worlds [26,27]. Although these are very interesting articles, they do not deal with the content of interest to us at all in terms of the application of these technologies to our energy-saving projects.…”
Section: Introductionmentioning
confidence: 99%